(untitled) (Modern Problems of Metallurgy, 2020)
Specialists of metallurgy and mechanical engineering are intensively working at materials with controlled properties. In fact, at this stage we are already talking about the design of new materials for the specific tasks of the industry. One of the ways to achieve the regulated mechanical properties of metal products is to use the influence of plastic deformation with its different parameters in individual sections of the deformable material. In this study, we studied the effect of cold rolling on the properties of a strip of aluminum alloy EN AW-1050 with artificially created differences in the deformation parameters in different parts of the cross section of the profile. For this, a pre-shaped sample was prepared by conducting joint cold rolling of a strip of the specified material 420 mm long, 180 mm wide and 2.9 mm thick with a steel profiling tape 80 mm wide and 2 mm thick superimposed on it (length of an aluminum strip and steel profiling tape are the same). As a result of joint deformation, the steel strip rolled into the base metal and changed the geometry of the cross section and the properties of the obtained strip. Next, the obtained strip was subjected to heat treatment and rolled in a duo mill. After rolling, thin samples were made from fabricated flat strips to assess mechanical properties, in particular tensile tests were performed according to ISO 6892-1: 2009 and Brinell hardness tests were performed according to ISO 6506-1: 2014. Experimental studies of cold rolling of strips with profiled cross section of aluminum alloy EN AW-1050 were carried out. The possibility of forming heterogeneous properties in a flat aluminum strip by cold plastic deformation is shown and the maximum average values of the increase in the main indicators of mechanical properties on individual elements of the strip are determined. The maximum difference between the mechanical properties of the thick and thin elements of the profiled strip is observed in the hardness index and reaches 37.5%. The maximum obtained average value of the increase in yield strength and tensile strength is 26% and 18%, which is achieved with true deformation of the thick element of the profiled strip 0.165 and 0.234.